Greece : First Post-Program Monitoring Discussions-Press Release; Staff Report; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Greece's First Post-Program Monitoring discussions. The economic recovery in Greece is accelerating and broadening. Growth and job creation in Greece are expected to accelerate further in 2019. However, vulnerabilities remain significant and downside risks are rising. Policies to promote stronger growth and strengthen the economy's resilience were the focus of the discussions. The discussion report emphasises on the importance of enhancing labor market flexibility and boosting productivity and competitiveness. Greece should reconsider recent changes in collective bargaining policies and press ahead with its unfinished reform agenda. This would also help mitigate any negative effects on competitiveness and employment from rising wage pressures. Speeding up efforts to clean up bank balance sheets, restore lending, and improve Greece's weak payment culture is also of prime importance. Medium-term public debt repayment capacity remains robust, but subject to rising risks amid still significant vulnerabilities.